Effects of regional tax, retribution, and Zakat Maslahah through local revenue - WIBISONO, C.; IRWANSYAH, H.; WIDIA, E.; FAIZAH, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In this study, the same sample is set with the population (census method) of respondents who were 195. Data analysis was performed using the Structural Equation Model (SEM). The software used for the structural analysis is AMOS 23 and Arbuckle and for descriptive analysis SPSS 23. So that the area Affects maslahah income for people in Batam City as the World Bandar Madani, it is necessary to make charity as a seed to regional and local income taxes that apply to lawful economic activities.RESUMEN En este estudio, la misma muestra se estableció con la población (método del censo) de los encuestados que fueron 195. El análisis de los datos se realizó utilizando el Modelo de ecuaciones estructurales (SEM). El software utilizado para el análisis estructural es AMOS 23 y Arbuckle y para el análisis descriptivo se uso el SPSS 23. Para que el área afecte el ingreso de maslahah para personas en la ciudad de Batam como World Bandar Madani, es necesario hacer que la caridad sea una semilla para los impuestos a la renta, regionales y locales que se aplican a las actividades económicas legales.